Effects of contraception pills and hormone replacementtherapy on VEGF and IL-6 in per and postmenopausal women (Eurasian Research Bulletin, 2023)
Contraception is a method of preventing pregnancy during the premenopausal period, whereas hormone replacement therapy (HRT) is a medical treatment used to treat menopausal issues. The purpose of this study was to look at the effects of contraception and HRT on Vascular endothelial growth factor (VEGF) and Interleukin-6 (IL-6). One hundred (120) women were recruited: 30 with contraception, 30 with HRT, and 60 with no contraception, with HRT, and 60 with no as a control group. All women were between the ages of 31 and 70 and were categorized into four groups (31–40, 41–50, 51–60, and 61–70 In comparison to control women (without contraception and hormonal replacement therapy), the results of this study showed a significant increase in VEFG levels in all tested women (p